The same but different?: a comparative lithic study of the Cave of Hearths Pietersburg and Klasies River MSA II techno-complexes - Oberholzer, Ronè (My University, 2021)
Middle Stone Age (MSA) lithic technology serves as a window into early Homo sapiens behaviour. The lithic technology within the MSA especially that predating the pre-Still Bay needs more intensive investigation from a comparative perspective to increase understanding of early Homo sapiens technology and occupation patterns. In recent studies, the Pietersburg has been compared to the MSA II while other studies refer to the Pietersburg as a regional expression confined to the interior of South Africa. In this study assemblages of the Pietersburg from Cave of Hearths (CoH) and MSA II from Klasies River Main site (KRM) were subjected to technological analysis following the chaîne opératoire approach. The comparison of these two assemblages revealed differences in flaking systems and implement types. In the Pietersburg assemblage preferential flake Levallois reduction methods dominated while platform reduction methods were most common in the MSA II assemblage. Techniques used to produce the blades and flakes in MSA II were ambiguous. The points from this assemblage, however, were probably made using hard hammer percussion technique. The Pietersburg blanks were all likely made using hard hammer percussion. Retouch was more common in the Pietersburg assemblage where unifacial points were a prominent tool type. No unifacial points were found in the MSA II assemblage and denticulates dominated. The interconnectedness between groups from the two sites during the MIS 5 was also investigated and it was concluded that coalescence between these two broadly contemporaneous sites during the MIS 5 is unlikely because of the dissimilarity of flaking systems and implement types. Based on the technological differences of the assemblages studied here the Pietersburg from CoHand MSA II from KRM do not form part of the same cultural entity, whether it be a techno-complex or industry
A dissertation is submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science for the School of Geography, Archaeology and Environmental Studies, 2021